PENGARUH PERUBAHAN ORGANISASI; BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI BADAN MANAJEMEN PUSAT PENGKAJIAN DAN PENGEMBANGAN ISLAM JAKARTA - Hasanah, Rina Uswatun; Aima, M. Havidz (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2018)
The purpose of this research is to determine and analyze the effect of organizational change; organizational culture; and motivation either partially or simultaneously on the performance of employees at the Management Institution Pusat Pengkajian dan Pengembangan Islam Jakarta (BM PPPIJ). The population in this research are 46 people with the respondent amounted allÂ  employees are sampling; research method using multiple linear regression analysis and descriptive analysis. Regression analysis was performed to determine wheter the independent variable (Organizational Change; Organizational Culture and Motivation) either partially or simultaneously affect the dependent variable (Performance Employees); and descriptive analysis conducted with data collection through the use of questionnaires to respondents. Results of research at the PPPIJ Institution shows that the variable of organizational change and organizational culture is not influence on employee performance; only motivation partially positive and significant influence on employee performance. Simultaneously; all three independent variables organizational change; organizational culture; and motivation positive and significant impact on employee performance PPPIJ Management Institution. In a test of the correlation between dimensions is obtained that the dimensions of technology at variable organizational change into the most dominant factor of the dimensions of cooperation abilities in the variable employee performance; dimensional of innovation and dare to take risks the variable of organizational culture becomes the most dominant factor of the dimensions of punctuality variable employee; and the dimensions of intrinsic motivation variable becomes the most dominant factor of the dimensions of cooperation abilities in the variable employee performance.